Low-speed, low induction multi-blade rotor for energy efficient small wind turbines - Yilmaz, Oktay (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
To promote the deployment of small wind turbines (SWTs), thorough understanding of design parameter im-plications is essential. In-depth research is required to comprehend the influence of design TSR on off-design wind speed performance of multi-blade SWTs. In-house built blade element momentum algorithm was employed, which considered Reynolds number dependence of aerodynamic coefficients and correlated well with experimental results. Peak power coefficients were produced for 0.9, 1.5, 2 and 3 m diameter S826 rotors with blade numbers from 2 to 12 and design TSR of 2-10. Remarkably, regardless of diameter, greatest CP,max values were achieved around design TSR of 4. For peak efficiency, smaller the diameter, narrower the blade number and design TSR range. High-speed rotors have wider TSR range for high power coefficient. Yet, it was shown that operating TSR of low-speed rotors deviates less from design TSR as wind speed varies. It was revealed that low-speed (with a threshold design TSR of 3), low-induction multi-blade rotors provide high CP,max, better efficiency at off-design, shorter starting time and lower wind speed than three-bladed high-speed rotor. A small boost in operational TSR was found to effectively mitigate loss in off-design performance. These are key features to maximize energy harvesting.
Keywords: Low induction rotor; Glauert optimum rotor; Design tip speed ratio; Blade number; Off-design performance; Starting capability; TURBULENCE MODELS; POWER CURVE; DESIGN; BLADE; PERFORMANCE; OPTIMIZATION; CFD; REDUCTION; HAWT; DRAG; Thermodynamics; Energy & Fuels